Answer:
Image attached
Step-by-step explanation:
Origin looks to be (0, -1), so move each point out by 2
Answer:
B
Step-by-step explanation:
5(c + ⁴/₅) + 6 = 50
5(c) + 5(⁴/₅) + 6 = 50
5c + 4 + 6 = 50
5c + 10 = 50
<u> - 10 - 10</u>
<u>5c</u> = <u>40</u>
5 5
c = 8
Answer:
Step-by-step explanation:
y-x=0.7
y=x+0.7, so lets plug in that into the expressions instead of y
1)
(y-x)=
x+0.7-x=
x+0.7+(-x)=
x+(-x)+0.7=
x-x+0.7=
0.7
2)
(x-(x+0.7))/((x+0.7)-x)=
(x-x+0.7)/(x+0.7-x)=
(x-x+0.7)/(x+0.7+(-x))=
(x-x+0.7)/(x+0.7+(-x))=
(x-x+0.7)/(x+(-x)+0.7)=
(x-x+0.7)/(x-x+0.7)=
0.7/0.7=
1